Infantile Mandibular Fracture Treatment with Double-crossed Skeletal and Circummandibular Wires: A Case Report - Alireza Khoshsirat; Sahand Samieirad; Maryam Hashemipour; Elahe Tohidi; Vajiheh Mianbandi (Mashhad University of Medical Sciences, 2019)
Abstract The prevalence of mandibular fracture is relatively lower in the pediatric population compared to adults. The treatment of these fractures is more challenging for oral and maxillofacial surgeons due to the concerns regarding mandible growth and the presence of developing tooth buds. According to the literature, conventional methods (e.g., soft diets or closed reduction) are more effective in the treatment of nondisplaced pediatric mandibular fractures. There are few case reports regarding the treatment of mandibular fractures in infants, which have mainly introduced new technique using double-crossed direct skeletal wires to reinforce circummandibular wirings for the conservative treatment of infantile mandibular fractures. The present study aimed to describe the case of a 12-month male infant with significant dislocated right mandibular parasymphysis fracture. Initially, two circummandibular wires were passed bilaterally to pull the mandibular segments for their vertical alignment. Afterwards, the skeletal buccal and lingual direct wires reinforced the previous circummandibular wiring to fit the fracture segments. Finally, all the wires were tightened simultaneously to maintain satisfactory bone reduction. Furthermore, the addition of skeletal buccal and lingual direct wires could reinforce the previous circummandibular wiring to fit the fracture segments anteroposteriorly. The fracture healed uneventfully with no complications, and intermaxillary fixation was not required in the patient. Moreover, the alveolar segments were in an appropriate position, and the maximum mouth opening of the patient was normal with no deviation, indicating a successful clinical outcome. This method was relatively reliable, noninvasive, and inexpensive, associated with the decreased discomfort and morbidity associated with maxillomandibular fixation, open reduction, and internal fixation in infants.